17 added 87 characters in body

HINT $\;$ Work "generically", i.e. let the entries $\;\rm a_{i,j}$ of $\rm A\;$ be indeterminates and work in the matrix ring $\rm M = M_n(R)\;$ over $\;\rm R = {\mathbb Z}[a_{i,j}\:]. \;$ We wish to prove $\rm B = C$ from $\rm d\: B = d\: C$ for $\rm d = det\: A \in R, \;\; B,C \in M.$ But this is equivalent to $\rm d\: b_{i,j} = d\: c_{i,j}$ in the domain $\rm R = {\mathbb Z}[a_{i,j}\:]$ where $\;\rm d = det\: A \ne 0$, so $\rm d$ is cancelable, yielding $\;\rm b_{i,j} = c_{i,j}\;$ hence $\rm B = C$. This identity remains true over every commutative ring $\rm S$ since, by the universality of polynomial rings, there exists an eval homomorphism that evaluates $\;\rm a_{i,j}\;$ at any $\;\rm s_{i,j}\in S$.

Notice that the crucial insight is that $\;\rm b_{i,j}\:, \; c_{i,j}\:,\; d\;$ have polynomial form in $\;\rm a_{i,j}\:$, i.e. they are elts of the polynomial ring $\;\rm R = {\mathbb Z}[a_{i,j}\:] = {\mathbb Z}[a_{1,1},\cdots,a_{n,n}\:]$ which, being a domain, enjoys cancelation of elts $\ne 0$. Working generically allows us to cancel $\rm d$ and deduce the identity before any evaluation where $\rm d\mapsto 0.$

Such proofs by way of universal polynomial identities emphasize the power of the abstraction of a formal polynomial (vs. polynomial function). Alas, many algebra textbooks fail to explicitly emphasize this universal viewpoint- leaving . As a result, many students often struggling with alternative dense cannot easily resist the obvious topological approachestemptations and instead derive hairier proofs employing density arguments (e.g see elswhere in this thread).

Analogously, the same generic method of proof works for many other polynomial identities, e.g.

$\rm\quad\; det(I-AB) = det(I-BA)\;\:$ by taking $\;\rm det\;$ of $\;\;\rm (I-AB)\;A = A\;(I-BA)\;$ then canceling $\;\rm det \:A$

$\rm\quad\quad det(adj \:A) = (det \:A)^{n-1}\quad$ by taking $\;\rm det\;$ of $\;\rm\quad A\;(adj\: A) = (det\: A) \;I\quad\;\;$ then canceling $\;\rm det \:A$

Now, for our pièce de résistance (of limits, density...)topology, we derive the polynomial derivative purely formally.

For $\rm f(x) \in R[x]$ define $\rm D f(x) = f_0(x,x)$ where $\rm f_0(x,y) = \frac{f(x)-f(y)}{x-y}.$ Note that the existence and uniqueness of this derivative follows from the Factor Theorem, i.e. $\;\rm x-y \; | \; f(x)-f(y)\;$ in $\;\rm R[x,y],\;$ and, from the cancelation law $\;\rm (x-y) g = (x-y) h \implies g = h$ for $\rm g,h \in R[x,y].$ It's clear this agrees on polynomials with the analytic derivative definition since it is linear and it takes the same value on the basis monomials $\rm x^n$. Resisting limits again, we get the product rule rule for derivatives from the trivial difference product rule

$$\rm f(x)g(x) - f(y)g(y)\; = \;(f(x)-f(y)) g(x) + f(y) (g(x)-g(y))$$

$\quad\quad\quad\quad\rm\quad\quad\quad \Longrightarrow \quad\quad\quad\quad\quad\; D(fg)\quad = \quad (Df) \; g \; + \; f \; (Dg)$

by canceling $\rm x-y$ in the first equation, then evaluating at $\rm y = x$, i.e. specialize the difference "quotient" from the product rule for differences. Here the formal cancelation of the factor $\;\rm x-y\;$ before evaluation at $\;\rm y = x\;$ is precisely analogous to the formal cancelation of $\;\rm det \:A\;$ in all of the examples given above.

16 Rollback to Revision 14

HINT $\;$ Work "generically", i.e. let the entries $\;\rm a_{i,j}$ of $\rm A\;$ be indeterminates and work in the matrix ring $\rm M = M_n(R)\;$ over $\;\rm R = {\mathbb Z}[a_{i,j}\:]. \;$ We wish to prove $\rm B = C$ from $\rm d\: B = d\: C$ for $\rm d = det\: A \in R, \;\; B,C \in M.$ But this is equivalent to $\rm d\: b_{i,j} = d\: c_{i,j}$ in the domain $\rm R = {\mathbb Z}[a_{i,j}\:]$ where $\;\rm d = det\: A \ne 0$, so $\rm d$ is cancelable, yielding $\;\rm b_{i,j} = c_{i,j}\;$ hence $\rm B = C$. This identity remains true over every commutative ring $\rm S$ since, by the universality of polynomial rings, there exists an eval homomorphism that evaluates $\;\rm a_{i,j}\;$ at any $\;\rm s_{i,j}\in S$.

Notice that the crucial insight is that $\;\rm b_{i,j}\:, \; c_{i,j}\:,\; d\;$ have polynomial form in $\;\rm a_{i,j}\:$, i.e. they are elts of the polynomial ring $\;\rm R = {\mathbb Z}[a_{i,j}\:] = {\mathbb Z}[a_{1,1},\cdots,a_{n,n}\:]$ which, being a domain, enjoys cancelation of elts $\ne 0$. Working generically allows us to cancel $\rm d$ and deduce the identity before any evaluation where $\rm d\mapsto 0.$

Such proofs by way of universal polynomial identities emphasize the power of the abstraction of a formal polynomial (vs. polynomial function). Alas, many algebra textbooks fail to explicitly emphasize this universal viewpoint - leaving students often struggling with alternative dense topological approaches.

Analogously, the same generic method of proof works for many other polynomial identities, e.g.

$\rm\quad\; det(I-AB) = det(I-BA)\;\:$ by taking $\;\rm det\;$ of $\;\;\rm (I-AB)\;A = A\;(I-BA)\;$ then canceling $\;\rm det \:A$

$\rm\quad\quad det(adj \:A) = (det \:A)^{n-1}\quad$ by taking $\;\rm det\;$ of $\;\rm\quad A\;(adj\: A) = (det\: A) \;I\quad\;\;$ then canceling $\;\rm det \:A$

Now, for our pièce de résistance (of limits, density...), we derive the polynomial derivative purely formally.

For $\rm f(x) \in R[x]$ define $\rm D f(x) = f_0(x,x)$ where $\rm f_0(x,y) = \frac{f(x)-f(y)}{x-y}.$ Note that the existence and uniqueness of this derivative follows from the Factor Theorem, i.e. $\;\rm x-y \; | \; f(x)-f(y)\;$ in $\;\rm R[x,y],\;$ and, from the cancelation law $\;\rm (x-y) g = (x-y) h \implies g = h$ for $\rm g,h \in R[x,y].$ It's clear this agrees on polynomials with the analytic derivative definition since it is linear and it takes the same value on the basis monomials $\rm x^n$. Resisting limits again, we get the product rule rule for derivatives from the trivial difference product rule

$$\rm f(x)g(x) - f(y)g(y)\; = \;(f(x)-f(y)) g(x) + f(y) (g(x)-g(y))$$

$\quad\quad\quad\quad\rm\quad\quad\quad \Longrightarrow \quad\quad\quad\quad\quad\; D(fg)\quad = \quad (Df) \; g \; + \; f \; (Dg)$

by canceling $\rm x-y$ in the first equation, then evaluating at $\rm y = x$, i.e. specialize the difference "quotient" from the product rule for differences. Here the formal cancelation of the factor $\;\rm x-y\;$ before evaluation at $\;\rm y = x\;$ is precisely analogous to the formal cancelation of $\rm \;\rm det \:A$ :A\;$in all of the example sparking this threadexamples given above. 15 Rollback to Revision 13 HINT$\;$Work "generically", i.e. let the entries$\;\rm a_{i,j}$of$\rm A\;$be indeterminates and work in the matrix ring$\rm M = M_n(R)\;$over$\;\rm R = {\mathbb Z}[a_{i,j}\:]. \;$We wish to prove$\rm B = C$from$\rm d\: B = d\: C$for$\rm d = det\: A \in R, \;\; B,C \in M.$But this is equivalent to$\rm d\: b_{i,j} = d\: c_{i,j}$in the domain$\rm R = {\mathbb Z}[a_{i,j}\:]$where$\;\rm d = det\: A \ne 0$, so$\rm d$is cancelable, yielding$\;\rm b_{i,j} = c_{i,j}\;$hence$\rm B = C$. This identity remains true over every commutative ring$\rm S$since, by the universality of polynomial rings, there exists an eval homomorphism that evaluates$\;\rm a_{i,j}\;$at any$\;\rm s_{i,j}\in S$. Notice that the crucial insight is that$\;\rm b_{i,j}\:, \; c_{i,j}\:,\; d\;$have polynomial form in$\;\rm a_{i,j}\:$, i.e. they are elts of the polynomial ring$\;\rm R = {\mathbb Z}[a_{i,j}\:] = {\mathbb Z}[a_{1,1},\cdots,a_{n,n}\:]$which, being a domain, enjoys cancelation of elts$\ne 0$. Working generically allows us to cancel$\rm d$and deduce the identity before any evaluation where$\rm d\mapsto 0.$Such proofs by way of universal polynomial identities emphasize the power of the abstraction of a formal polynomial (vs. polynomial function). Alas, many algebra textbooks fail to explicitly emphasize this universal viewpoint - leaving students often struggling with alternative dense topological approaches. Analogously, the same generic method of proof works for many other polynomial identities, e.g.$\rm\quad\; det(I-AB) = det(I-BA)\;\:$by taking$\;\rm det\;$of$\;\;\rm (I-AB)\;A = A\;(I-BA)\;$then canceling$\;\rm det \:A\rm\quad\quad det(adj \:A) = (det \:A)^{n-1}\quad$by taking$\;\rm det\;$of$\;\rm\quad A\;(adj\: A) = (det\: A) \;I\quad\;\;$then canceling$\;\rm det \:A$Now, for our pièce de résistance (of limits, density...), we derive the polynomial derivative purely formally. For$\rm f(x) \in R[x]$define$\rm D f(x) = f_0(x,x)$where$\rm f_0(x,y) = \frac{f(x)-f(y)}{x-y}.$Note that the existence and uniqueness of this derivative follows from the Factor Theorem, i.e.$\;\rm x-y \; | \; f(x)-f(y)\;$in$\;\rm R[x,y],\;$and, from the cancelation law$\;\rm (x-y) g = (x-y) h \implies g = h$for$\rm g,h \in R[x,y].$It's clear this agrees on polynomials with the analytic derivative definition since it is linear and it takes the same value on the basis monomials$\rm x^n$. Resisting limits again, we get the product rule rule for derivatives from the trivial difference product rule $$\rm f(x)g(x) - f(y)g(y)\; = \;(f(x)-f(y)) g(x) + f(y) (g(x)-g(y))$$$\quad\quad\quad\quad\rm\quad\quad\quad \Longrightarrow \quad\quad\quad\quad\quad\; D(fg)\quad = \quad (Df) \; g \; + \; f \; (Dg) $by canceling$\rm x-y$in the first equation, then evaluating at$\rm y = x$, i.e. specialize the difference "quotient" from the product rule for differences. Here the formal cancelation of the factor$\;\rm x-y\;$before evaluation at$\;\rm y = x\;$is precisely analogous to the formal cancelation of$\;\rm \rm det \:A\;$:A$ in all of the examples given aboveexample sparking this thread.

14 added 4 characters in body
13 added 38 characters in body; deleted 1 characters in body; added 5 characters in body